Merdeka Belajar is Reflected in the Professional Competence of English Teachers - Siti Sudaryani; Munawaroh, Diah Ambarumi (JEET, Journal of English Education and Technology, 2022)
"Merdeka Belajar (autonomous learning) is a term that emphasizes the freedom and responsibility of students in learning. In this regard, English teachers have an essential role in reflecting their professional competence by facilitating an independent learning process for students. It involves providing appropriate direction and guidance and ensuring that students have sufficient access to resources and technology to assist them in learning effectively and independently. That way, students can reach their potential and build the skills necessary to succeed in a competitive global world. This study uses a qualitative descriptive approach with obsession, interviews, and documentation. The results showed that independent learning is an effective learning process and gives responsibility to students. In addition, English teachers also have an essential role in facilitating the process of independent learning because the professional competence of English teachers determines the success of the autonomous learning process. Further research can focus more on learning models that support and facilitate students to be independent in learning.